Partículas modais da língua portuguesa : relances contrastivos com as partículas alemãs - Franco, António Capataz (2012)
Although the category or sub-category modal particles (MPs) is - as such - unknown to Portuguese grammarians and lexicographers, the Portuguese spoken and written language does, in fact, use these lexical units. They present some syntactic features identical to those of German MPs, but their distribution in the sentence, compared with the latter, involves essential differences in their semantics and pragmatics. This paper not only shows how particles such as e que and sempre are employed, and what functions they can assume in certain types of utterances, but also indicates their respective equivalents in German.